(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The current article extends a comprehensive analysis of innovative ELT (English Language Teaching) classroom methods for teaching English. The objective is to investigate the fundamental principles, theoretical underpinnings, examples of activities/strategies, benefits, prospective challenges, and research findings associated with each method. By synthesizing the existing literature, this paper highlights the significance of incorporating innovative methods in ELT and their potential to improve language learning outcomes, learner engagement, and motivation. The methodology of the study included a systematic literature search to identify relevant studies. We utilized ERIC, Education Source, Scopus, and Google Scholar databases with keywords and search terms on innovative methods, ELT, teaching English, language acquisition, and implementation. Filter based on publication dates, language, and journals with peer review was implemented to refine the search results. The selection procedure included evaluating the relevance of article titles and abstracts to the research objectives and inclusion criteria. For in-depth analysis, full-text articles meeting the inclusion criteria were obtained. The inclusion/exclusion criteria included research quality, relevance to the topic, methodology employed, and the availability of empirical evidence. The findings of the examined studies highlight the importance of innovative ELT methods. These strategies emphasize learner engagement, meaningful communication, critical thinking, and problem-solving abilities. Educators frequently utilize technology, authentic materials, real-world duties, and interactive activities to create dynamic and engaging learning environments. Consistently, research has shown that innovative methods enhance learner motivation, language-learning outcomes, and engagement. The implications for practice suggest that ELT practitioners should embrace learner-centered approaches, incorporate various innovative methods, encourage learner autonomy and critical thinking, utilize technology and digital resources, and consider contextual factors when implementing these methods. In addition, programmes for professional development and ongoing reflection are recommended to assist teachers in integrating innovative methods into their classrooms. This review paper concludes by emphasizing the significance of innovative methods in ELT and their potential to improve language learning outcomes and student engagement. This paper lays the groundwork for ELT practitioners to employ innovative approaches and create dynamic and effective learning environments by exploring these methods’ fundamental principles, benefits, and challenges. To further advance the field of innovative ELT practises, future research should address gaps, assess long-term effects, and investigate emergent trends and technologies.